Structure and function in rhodopsin: the role of asparagine-linked glycosylation. - Kaushal, S (1994)
Rhodopsin, the dim light photoreceptor of the rod cell, is an integral membrane protein that is glycosylated at Asn-2 and Asn-15. Here we report experiments on the role of the glycosylation in rhodopsin folding and function. Nonglycosylated opsin was prepared by expression of a wild-type bovine opsin gene in COS-1 cells in the presence of tunicamycin, an inhibitor of asparagine-linked glycosylation. The non-glycosylated opsin folded correctly as shown by its normal palmitoylation, transport to the cell surface, and the formation of the characteristic rhodopsin chromophore (lambda max, 500 nm) with 11-cis-retinal. However, the nonglycosylated rhodopsin showed strikingly low light-dependent activation of GT at concentration levels comparable with those of glycosylated rhodopsin. Amino acid replacements at positions 2 and 15 and the cognate tripeptide consensus sequence [Asn-2-->Gln, Gly-3-->Cys(Pro), Thr-4-->Lys, Asn-15-->Ala(Cys, Glu, Lys, Gln, Arg), Lys-16-->Cys(Arg), Thr-17-->Met(Val)] showed that the substitutions at Asn-2, Gly-3, and Thr-4 had no significant effect on the folding, cellular transport, and/or function of rhodopsin, whereas those at Asn-15 and Lys-16 caused poor folding and were defective in transport to the cell surface. Further, mutant pigments with amino acid replacements at Asn-15 and Thr-17 activated GT very poorly. We conclude that Asn-15 glycosylation is important in signal transduction.